2021
DOI: 10.3892/ol.2021.12736
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the association between KIN17 expression and the clinical features/prognosis of epithelial ovarian cancer, and the effects of KIN17 in SKOV3 cells

Abstract: DNA double-strand breaks (DSBs) are an important mechanism of chemotherapy in epithelial ovarian cancer (EOC). Kin17 DNA and RNA binding protein (KIN17) serves a crucial role in DSB repair. In the present study, the association between KIN17 and EOC, and the effects of KIN17 on EOC cells in vitro were evaluated. A bioinformatics method was used to determine the mRNA expression levels of KIN17 in EOC and its association with EOC prognosis including overall survival (OS) and progression fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…In addition to univariate analysis and Kaplan-Meier survival analysis, multivariate Cox regression analysis suggested that KIN17 and the tumor stage were independent prognostic factors in EOC. However, there was no association between the localization (cytoplasm or nucleus) of KIN17 and the overall survival (64).…”
Section: Roles Of Kin17 In Cancer Cellsmentioning
confidence: 85%
“…In addition to univariate analysis and Kaplan-Meier survival analysis, multivariate Cox regression analysis suggested that KIN17 and the tumor stage were independent prognostic factors in EOC. However, there was no association between the localization (cytoplasm or nucleus) of KIN17 and the overall survival (64).…”
Section: Roles Of Kin17 In Cancer Cellsmentioning
confidence: 85%
“…Finally, the slides were imaged using an Olympus optical microscope (BX51). The evaluation criteria were based on staining intensity and the proportion of positive tumour cells as previously described 26 . For staining intensity: 0 (no colour), 1 (light yellow), 2 (yellow brown), and 3 (brown).…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation criteria were based on staining intensity and the proportion of positive tumour cells as previously described. 26 For staining intensity: 0 (no colour), 1 (light yellow), 2 (yellow brown), and 3 (brown). For the proportion of positive tumour cells: 0 (<5%), 1 (5%-25%), 2 (26%-50%), 3 (51%-75%), and 4 (>75%).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemistry. Immunohistochemical (IHC) staining was performed as previously described (23). Briefly, after being fixed in 10% formalin at room temperature for 24 h, PCa samples or mouse tumour samples were embedded in paraffin and cut into 3-µm-thick sections.…”
Section: Methodsmentioning
confidence: 99%